A folia de momo na cidade de São Paulo na percepção da imprensa e dos artistas do traço: 1960/1964 - Silva, Zélia Lopes da [UNESP] (My University, 2013)
The discussion of this paper focuses on the search for demarcation of the Momo merriments in the city of São Paulo between 1960 and 1964, aiming to apprehend their specific traits at that juncture. It is known that the Brazilian Carnival, and in its sphere the São Paulo City one, has been steadily becoming enshrined in profile by popular segments. However, in that decade onset such festivities were going through certain peculiarities because it was a period characterized by many changes. The city of São Paulo, particularly, was experiencing an accelerated process of urbanization and consequent massification, as well as a moment of significant expansion of the cultural industry and mass communication means. Were the Momo revels immune to this process? What was the profile of these amusements in the city?

A discussão deste texto centra-se na busca de demarcação dos folguedos de Momo na cidade de São Paulo, entre 1960 e 1964, com o objetivo de apreender, na conjuntura, os seus traços específicos.Sabe-se que o carnaval brasileiro e, em seu âmbito o paulistano, paulatinamente vem se tornando de perfil plasmado pelos segmentos populares. Porém, nesse início de década esses festejos atravessam certas peculiaridades por se tratar de um período caracterizado por muitas transformações, particularmente na cidade de São Paulo que vivencia processo acelerado de urbanização e de massificação daí decorrente, bem como momento de significativa expansão da indústria cultural e dos meios de comunicação de massa. As brincadeiras de Momo ficaram imunes a esse processo? Qual o perfil desses folguedos na cidade?
Keywords: Carnival celebrations and caricature; São Paulo City carnivals; Press and carnivals; Festejos carnavalescos e caricatura; Carnavais paulistanos; Imprensa e carnavais